Effect of supplementing phytase on piglet performance, nutrient digestibility and bone mineralisation - C. De Cuyper; L. Nollet; M. Aluwé; J. De Boever; L. Douidah; E. Vanderbeke; N. Outchkourov; S. Petkov; S. Millet (Journal of Applied Animal Nutrition)
Incremental levels of the phytase, OptiPhos® Plus, were fed to 150 weaned piglets (five treatments of 30 pigs) to determine the effect on piglet performance, nutrient digestibility and bone mineralisation. Piglets were fed a basal diet from four to six weeks and a pre-starter diet from six to ten weeks of age. The basal diets contained reduced digestible phosphorus (P) and calcium (Ca) (1.5 g/kg digestible P, and Ca 5.5 g/kg and 5.6 g/kg for weaner and pre-starter, respectively) to provide a negative control. Phytase was added at 0, 125, 250, 500 and 1000 phytase units (FTU)/kg feed. Faecal samples were collected at nine weeks of age and analysed for P, Ca and crude protein (CP) content to calculated digestibility. Metacarpal bone IV mineralisation was assessed by ash content and the weight and length of the bone. Incremental increases of phytase improved final body weight (BW) (P<0.001), average daily gain (ADG) (P<0.001) and feed conversion ratio (FCR) (P<0.01). The statistical model predicted a linear increase for daily feed intake (DFI), ADG and BW with increased phytase increments. BW at the end of the trial increased by 824 g per increase of 250 FTU/kg (P<0.001). ADG and DFI increased by 19 g/day (P<0.001) and 18 g/day (P<0.05) respectively, per increase of 250 FTU/kg. As the effect on ADG and final BW was higher at lowest doses, a quadratic effect for these parameters was observed, within the measured range of phytase levels (P=0.029 and 0.028, respectively). A reduction of 0.03 in FCR was observed for each 250 FTU/kg increase (P<0.01). For each increase in 250 FTU/kg, bone dry weight increased by 131 g (P<0.05) and bone ash concentration by 1.9% of fat free dry matter (P<0.001). The results showed that the addition of phytase to piglet diets low in P led to better utilisation of phytate-P and consequently better piglet performance.